The Global, Regional, and National Burden of Young‐Onset Dementia: An Updated Analysis of the Global Burden of Disease Study 2021 - Yang Zhao; Tai‐Yi Sun; Rui Zhang; Yu‐Hui Liu; Yan‐Jiang Wang (Brain Health, 2026)
ABSTRACT Young‐onset dementia (YOD), defined as dementia with onset between 40 and 65 years of age, is an emerging global health concern associated with substantial healthcare and socioeconomic burdens. Using data from the Global Burden of Disease Study 2021, this population‐based study analyzed trends in the prevalence, death rates, and disability‐adjusted life years (DALYs) of YOD across 204 countries and territories from 1990 to 2021. In 2021, there were 7.76 million prevalent cases of YOD worldwide, representing a 111.1% increase from 3.68 million in 1990. Decomposition analysis showed that population growth was the main contributor to the increase in the number of prevalent cases. The global age‐standardized prevalence rose slightly from 345.94 (95% UI: 259.46–448.88) to 355.93 (95% UI: 267.19–462.75) per 100,000 population (estimated annual percentage change [EAPC] 0.07, 95% CI: 0.06–0.08). Prevalence, death rates, and DALY rates were consistently higher among females than among males, with the highest burden observed in the 60–64 age group. From 1990 to 2021, DALYs attributable to high fasting plasma glucose and high body mass index showed upward trends globally (EAPCs of 1.25 and 2.13, respectively), while those attributable to tobacco use declined (EAPC −0.75). These findings indicate that the absolute global burden of YOD has increased substantially. Public health responses should therefore distinguish demographic‐driven increases in case numbers from changes in underlying disease occurrence, while strengthening prevention strategies targeting modifiable metabolic risk factors, early diagnosis, and resource allocation.